2021
DOI: 10.26650/ibr.2021.51.0117
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Forecasting Performance of ARIMA LSTM and HYBRID Models for The Sales Volume Budget of a Manufacturing Enterprise

Abstract: This study aims to create a monthly sales quantity budget by making use of the previous income data of an enterprise operating within the construction sector, which is considered the locomotive of the economy. For estimating time-series of sales as a linear model ARIMA (Auto-Regressive Integrated Moving Average), as nonlinear model LSTM (Long Short-Term Memory) and a HYBRID (LSTM and ARIMA) model built to improve system performance compared to a single model was used. As a result of the study, Mean Square Erro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…MAE quantifies the average magnitude of errors between predicted and actual values. It offers an insight into the accuracy of the model, focusing on the size of the errors without taking into account the direction of these errors [54]. MSE computes the average of the squares of the errors.…”
Section: Results Imputationmentioning
confidence: 99%
“…MAE quantifies the average magnitude of errors between predicted and actual values. It offers an insight into the accuracy of the model, focusing on the size of the errors without taking into account the direction of these errors [54]. MSE computes the average of the squares of the errors.…”
Section: Results Imputationmentioning
confidence: 99%
“…The obtained result with hybrid models were individually compared, it was observed that they could reduce the general variance or error, even if they are unrelated. Due to this reason, hybrid models are recognized as the most successful models for forecasting tasks [15]. This information will support the decision makers for energy management and decarbonization planning.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, it has become evident that hybrid methods yielded better results compared to a single method. A summary of studies that applied hybrid model for accurate prediction: Soy Temür et al [15] proposed a hybrid model which consists of a combination of the linear model (ARIMA), nonlinear model (LSTM), and hybrid (LSTM and ARIMA) model to improve system performance compared to a single model. A prediction method (GA-CNN-LSTM) combines a convolutional neural network (CNN) and a long-short-term memory network (LSTM) and is optimized by a genetic algorithm (GA) [16].…”
Section: Related Work On Arima-lstmmentioning
confidence: 99%
See 1 more Smart Citation
“…It is mainly utilized in deep learning that performs better on substantial datasets. The outcome of this test is that they can repeat their achievement with a 13 percent -16 percentage error margin [13]. LSTMs are a form of RNN that focuses on learning longterm dependency.…”
Section: Literature Reviewmentioning
confidence: 99%